PENERAPAN SISTEM TIKET ELEKTRONIK PERUSAHAAN BUS ANTAR KOTA PADA TERMINAL TERPADU - Abdul Gani Kamaludin; Nuraini Puspitasari; Deden Galih Ginanjar (Institut Transportasi dan Logistik Trisakti, 2017)
Pulo Gebang integrated terminal is the biggest terminal in South-East Asia which was opened and launched in December 2016. As it was planned, all the inter city bus companies, operating in Pulo Gadung and Rawa Mangun terminals, would be moved to Pulo Gebang integrated terminal. The objective of this research is to find out the development of electronic ticket system at Pulo Gebang integrated terminal, Jakarta; the constraining factors in improving the electronic ticket system; and the basic problem of electronic ticket booking system. The method used in this research was Fishbone method. Research data were gathered by taking random sampling from 20 respondents. The result of the research shows the median of percentage limit is 65%, therefore, 4 problems are arisen from 10 questions which reveals that there are only a small number of activities in the electronic ticket booking system and its promotions.